2016
DOI: 10.1016/j.jadohealth.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of E-Cigarette Perceptions and Trial Among Early Adolescents in Mexico

Abstract: PURPOSE Assess the prevalence and correlates of e-cigarette perceptions and trial among adolescents in Mexico, where e-cigarettes are banned. METHODS Cross-sectional data were collected in 2015 from a representative sample of middle school students (n=10,146). Prevalence of e-cigarette awareness, relative harm, and trial were estimated, adjusting for sampling weights and school-level clustering. Multilevel logistic regression models adjusted for school-level clustering to assess correlates of e-cigarette awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
88
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 30 publications
13
88
2
3
Order By: Relevance
“…Results from the present study are consistent with previous research that has investigated the association between sensation seeking and ever use of tobacco products in adolescents (Hampson et al, 2015; Hanewinkel & Isensee, 2015; Hanewinkel, Isensee, Sargent, & - Morgenstern, 2011; Primack et al, 2015; Thrasher et al, 2016; Wills et al, 2015); however, much of the previous research has been cross-sectional. Similar to the longitudinal study conducted by Hanewinkel and Isensee (2015), the present study found that higher sensation seeking was associated with increased odds of ever e-cigarette use over time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results from the present study are consistent with previous research that has investigated the association between sensation seeking and ever use of tobacco products in adolescents (Hampson et al, 2015; Hanewinkel & Isensee, 2015; Hanewinkel, Isensee, Sargent, & - Morgenstern, 2011; Primack et al, 2015; Thrasher et al, 2016; Wills et al, 2015); however, much of the previous research has been cross-sectional. Similar to the longitudinal study conducted by Hanewinkel and Isensee (2015), the present study found that higher sensation seeking was associated with increased odds of ever e-cigarette use over time.…”
Section: Discussionsupporting
confidence: 90%
“…To date, five studies have examined the association between sensation seeking and e-cigarette use behaviors, providing preliminary indication that high sensation seeking is associated with ever e-cigarette use in adolescents (Hampson, Andrews, Severson, & Barckley, 2015; Hanewinkel & Isensee, 2015; Primack et al, 2015; Thrasher et al, 2016; Wills et al, 2015). In a cross-sectional study of Hawaiian adolescents, Wills et al (2015) found that mean sensation seeking scores were significantly higher for 1) ever e-cigarette only users as compared to non-users, and 2) ever dual users of both e-cigarettes and conventional cigarette users as compared to e-cigarette only users.…”
Section: Introductionmentioning
confidence: 99%
“…The correlates of trying e-cigarettes appear generally similar to those reported for cigarettes and can be divided into three mayor domains: sociodemographics (i.e., sex, age, parental education, type of school), personal risk (i.e., sensation seeking, prior cigarette use, other substance use) and network influences (i.e., friend smoking, household smoking and parenting style). Being male, having lower parental support, higher rebelliousness, peer tobacco use, and advertising exposures has been associated with trying an e-cigarette 3,8,[16][17][18][19][20] . Alcohol and other drugs use have also been associated 3,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol and other drugs use have also been associated 3,21 . Beyond these more traditional risk factors for conventional cigarettes, the Mexican study indicated that trial of e-cigarettes was associated with more specific risk factors like greater utilization of electronic media devices (i.e., "technophilia"), bedroom Internet access, and Internet advertising exposures 8 . These risk factors may be particularly important in countries such as Argentina, that have banned e-cigarettes, as Internet can provide uncensored information including e-cigarette marketing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation